Birds, birds, birds: Co-worker similarity, workplace diversity, and voluntary turnover - Boris Hirsch; Elke J. Jahn; Thomas Zwick (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2019)
We investigate how the demographic composition of the workforce along the sex, nationality, education, age, and tenure dimension affects voluntary turnover. Fitting duration models for workers' job-to-job moves that control for workplace fixed effects in a representative sample of large manufacturing plants in Germany during 1975-2016, we find that larger co-worker similarity in all five dimensions substantially depresses voluntary turnover whereas workplace diversity is of limited importance. In line with conventional wisdom, which has that birds of one feather flock together, our results suggest that workers prefer having co-workers of their kind and place less value on diverse workplaces.
Keywords: J63; J62; J21; J19; 330; workforce demography; co-worker similarity; workplace diversity; voluntary turnover